The use of interactive teaching methods in the training of sports coaches in universities in Сhina - Zhai Xingchen; Ryzhkova L.G.; Go Erni (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the level of demand for interactive teaching methods when conducting classes aimed at acquiring special knowledge, professional skills and abilities from future table tennis coaches. Methods and structure of the study. To achieve this goal, an expert survey was conducted, in which 9 teachers from Zhengzhou Sports University and 4 teachers from RUS «GTSOLIFK» took part. Experts were asked to express their opinion on the use and significance of interactive methods when conducting practical classes aimed at acquiring special knowledge, professional skills and abilities from students. All respondents were highly qualified table tennis specialists and had more than 10 years of teaching experience. Results and conclusions. The results of an expert survey to assess the applicability of interactive teaching methods in the educational process with students of sports universities (W = 0.897), focused on training table tennis coaches, indicate that teachers most often use this method as training, and 61.5% of respondents put it in 1st place, and 38.5% - in 2nd. In addition, it is necessary to highlight the applicability of the modeling method, and 61.5% of respondents put it in 2nd place, but 38.5% highlight it as the main one, putting it in 1st place. However, when assessing the significance of the interactive teaching methods used in practical classes with students specializing in table tennis, the experts identified, first of all, role-playing as the most effective method of training coaches (W = 0.874). This is explained by the fact that in a role-playing game attention, perception, memory, imagination are activated, and the cognitive, emotional and behavioral aspects of the simulated situations are realized.